2014
DOI: 10.1111/gcb.12475
|View full text |Cite
|
Sign up to set email alerts
|

Soil C and N availability determine the priming effect: microbial N mining and stoichiometric decomposition theories

Abstract: The increasing input of anthropogenically derived nitrogen (N) to ecosystems raises a crucial question: how does available N modify the decomposer community and thus affects the mineralization of soil organic matter (SOM). Moreover, N input modifies the priming effect (PE), that is, the effect of fresh organics on the microbial decomposition of SOM. We studied the interactive effects of C and N on SOM mineralization (by natural (13) C labelling adding C4 -sucrose or C4 -maize straw to C3 -soil) in relation to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

43
541
1
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 872 publications
(589 citation statements)
references
References 76 publications
43
541
1
4
Order By: Relevance
“…Despite extensive work on the subject, the degree to which C chemistry alone drives the decomposition of litter and soil in response to elevated temperatures is frequently debated (Giardina and Ryan, 2000;Bol et al, 2003;Fierer et al, 2005;Knorr et al, 2005;Bauer et al, 2008;Conant et al, 2008;Craine et al, 2010;Hopkins et al, 2012;Suseela et al, 2013;Lefevre et al, 2014), as is the response of soil-C to N addition (Melillo et al, 2002;Neff et al, 2002;Auyeung et al, 2013). Part of this confusion may lie in the impact and influence of microbial community structure and function, as it has been shown as a potential driver of soil C turnover in response to N (Billings and Ziegler, 2008;Chen et al, 2014;Kaiser et al, 2014), warming (Bardgett et al, 2008;Balser and Wixon, 2009;Yuste et al, 2011;Zhou et al, 2012;Nie et al, 2013;Ziegler et al, 2013;Hopkins et al, 2014;Wei et al, 2014), and the interactive effects of N and warming (Cusack et al, 2010;Li et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Despite extensive work on the subject, the degree to which C chemistry alone drives the decomposition of litter and soil in response to elevated temperatures is frequently debated (Giardina and Ryan, 2000;Bol et al, 2003;Fierer et al, 2005;Knorr et al, 2005;Bauer et al, 2008;Conant et al, 2008;Craine et al, 2010;Hopkins et al, 2012;Suseela et al, 2013;Lefevre et al, 2014), as is the response of soil-C to N addition (Melillo et al, 2002;Neff et al, 2002;Auyeung et al, 2013). Part of this confusion may lie in the impact and influence of microbial community structure and function, as it has been shown as a potential driver of soil C turnover in response to N (Billings and Ziegler, 2008;Chen et al, 2014;Kaiser et al, 2014), warming (Bardgett et al, 2008;Balser and Wixon, 2009;Yuste et al, 2011;Zhou et al, 2012;Nie et al, 2013;Ziegler et al, 2013;Hopkins et al, 2014;Wei et al, 2014), and the interactive effects of N and warming (Cusack et al, 2010;Li et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…As TN did not change significantly over time, the SOC/TN ratio increased, particularly in the top 0.2 m under Sinensis. This may reflect the high C/N ratio of the source material: the C/N ratio of Miscanthus roots can exceed 40 (data not presented) suggesting that microbial N mining may control the decomposition of organic C, thereby increasing potential C sequestration rates, and the maintenance of poor TN contents in this N-limited system [41].…”
Section: Soc and Tn Under Bioenergy Cropsmentioning
confidence: 99%
“…Enzyme activities, such as β-glucosidase, cellobiohydrolase, chitinase and acid phosphatase are involved in C, N and P cycling and catalyze organic matter decomposition and nutrient mineralization. These key soil enzymes have been used extensively in soil research as their activities have been shown to be sensitive to land-use change [23]- [25]. The availability of soil nutrient to plants is important for ensuring agricultural sustainability.…”
Section: Introductionmentioning
confidence: 99%